Upaya Membangun Skema Kerjasama Penempatan Praktek Laut/Darat Taruna Politeknik Pelayaran Barombong pada Perusahaan Pelayaran dan Pengelola Pelabuhan - Abu Bakar; Sidrotul Muntaha; Ahmad Fauzi; Adnan (Hengkara Majaya, 2024)
Merchant Marine Polytechnic (Poltekpel) Barombong is a public university within the Ministry of Transportation of the Republic of Indonesia which is under and responsible for organizing vocational education, research, and, and community service in the field of shipping which was established on June 28, 1980 under the name of the Basic Sailing Education and Training Center (BPLPD) Barombong and With the Regulation of the Minister of Transportation of the Republic of Indonesia (PM) number PM 29 Year 2019 dated April 15, 2019, BP2IP Barombong changed its institution to Polytechnic of Shipping Barombong. Placement of Prala Taruna/Prada is an absolute obligation must be planned by educational institutions to ensure that all students are able to be facilitated to get a place of implementation of Prala and Prada according to Vision Mission.Therefore this research aims to know the extent of the scheme of cooperation efforts carried out by Poltekpel Barombong with Shipping Companies, SOEs and Government Agencies for placement and knowing how the scheme of the process of setting up/placement of prala/prada for Taruna Poltekpel Barombong. This research is descriptive qualitative research with data collection, observation, interviews, and documentation. Observation is done by looking at and observing how to report the sign off of Prala by post-prala cadets, conducting interviews with respondents who have disembarked from the ship and analyzing complete report file documents and using the survey method of collecting data from a sample of the population to represent the entire population as a data collection tool. D-III Program with the number of 54 Midshipmen all declare Prala/Prada looking for its own Company, DP-III Establishment Program with the number of 32 Midshipmen all declare Prala/Prada is looking for its own Company and DP-IV Establishment Program with a total of 41 Midshipmen all stating Prala/Prada is looking for its own Company. From the results of the data analysis shown as many as 384 shipping companies in six cities in Indonesia and as many as 1,483 in nine countries, opportunities and percentage of cadets placement of marine practices and land practices Polytechnic of Marine Barombong, have the opportunity to be improved by creating and implementing a cooperation scheme placement of Prala/Prada Taruna. ABSTRAK Politeknik Pelayaran (Poltekpel) Barombong merupakan perguruan tinggi negeri di lingkungan Kementerian Perhubungan Republik Indonesia yang berada di bawah dan bertanggung jawab menyelenggarakan program pendidikan vokasi, penelitian, dan pengabdian kepada masyarakat di bidang pelayaran yang didirikan pada tanggal 28 Juni 1980 dengan nama Balai Pendidikan dan Latihan Pelayaran Dasar (BPLPD) Barombong dan Dengan Peraturan Menteri Perhubungan RI (PM) Nomor PM 29 Tahun 2019 tanggal 15 April 2019, BP2IP Barombong berubah kelembagaan menjadi Politeknik Pelayaran Barombong. Penempatan Taruna Prala/Prada menjadi kewajiban yang mutlak harus direncanakan oleh lembaga pendidikan untuk memastikan bahwa semua anak didik mampuh difasilitasi untuk mendapatkan tempat pelaksanaan Prala dan Prada sesuai Visi Misi.Oleh karena itu penelitian ini bertujuan untuk mengetahui sejauh mana upaya skema kerja sama yang dilakukan oleh Poltekpel Barombong dengan Perusahaan Pelayaran, BUMN dan Instansi Pemerintah untuk penempatan dan mengetahui bagaimana skema proses pengaturan /penempatan prala/prada bagi Taruna Poltekpel Barombong. Penelitian ini merupakan penelitian kualitatif deskriptif dengan pengumpulan data, melakukan observasi, wawancara, dan dokumentasi. Observasi dilakukan dengan cara melihat dan mengamati cara pelaporan sign off Prala oleh para taruna pasca prala, melakukan wawancara terhadap responden yang sudah turun dari kapal dan menganalisa dokumen berkas laporan lengkap serta menggunakan metode pendekatan survey pengumpulan data-datanya dari sampel atas populasi untuk mewakili seluruh populasi sebagai alat pengumpul data. Program D-III dengan jumlah 54 Taruna semua menyatakan Prala/Prada mencari sendiri Perusahaan, Program DP-III Pembentukan dengan jumlah 32 Taruna semua menyatakan Prala/Prada mencari sendiri Perusahaan dan Program DP-IV Pembentukan dengan jumlah 41 Taruna semua menyatakan Prala/Prada mencari sendiri Perusahaan. Dari hasil analisis data yang ditampilkan sebanyak 384 perusahaan pelayaran di enam kota di Indonesia dan sebanyak 1.483 pada sembilan negara, peluang dan presentase penempatan taruna praktek laut dan praktek darat Politeknik Pelayaran Barombong, mempunyai peluang kedepan untuk ditingkatkan dengan membuat dan menerapkan skema kerjasama Penempatan Taruna Prala/Prada.